2023
DOI: 10.3390/v15102063
|View full text |Cite
|
Sign up to set email alerts
|

Structural Investigations of Interactions between the Influenza a Virus NS1 and Host Cellular Proteins

Morgan E. Blake,
Alex B. Kleinpeter,
Alexander S. Jureka
et al.

Abstract: The Influenza A virus is a continuous threat to public health that causes yearly epidemics with the ever-present threat of the virus becoming the next pandemic. Due to increasing levels of resistance, several of our previously used antivirals have been rendered useless. There is a strong need for new antivirals that are less likely to be susceptible to mutations. One strategy to achieve this goal is structure-based drug development. By understanding the minute details of protein structure, we can develop antiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 237 publications
0
5
0
Order By: Relevance
“…The IAV NS1 LP between the RBD and ED is mostly made of 11 aa residues (74-85) ( Hale et al., 2008b ). The majority of IAV H5N1 isolates circulating after 2003 displayed a 5 aa deletion from residues 80 to 84 in the LP ( Figure 2A ) ( Blake et al., 2023 ). Despite that the exact role of the LP in not fully understood, studies showed that it is crucial for the distinct properties of IAV NS1 because it controls the large conformational changes required to switch from the ‘helix-open’ to ‘helix-closed’ state and vice versa ( Kerry et al., 2011 ; Hale, 2014 ).…”
Section: Iav Ns1 and Sars-cov-2 Nsp1 Structuresmentioning
confidence: 99%
See 3 more Smart Citations
“…The IAV NS1 LP between the RBD and ED is mostly made of 11 aa residues (74-85) ( Hale et al., 2008b ). The majority of IAV H5N1 isolates circulating after 2003 displayed a 5 aa deletion from residues 80 to 84 in the LP ( Figure 2A ) ( Blake et al., 2023 ). Despite that the exact role of the LP in not fully understood, studies showed that it is crucial for the distinct properties of IAV NS1 because it controls the large conformational changes required to switch from the ‘helix-open’ to ‘helix-closed’ state and vice versa ( Kerry et al., 2011 ; Hale, 2014 ).…”
Section: Iav Ns1 and Sars-cov-2 Nsp1 Structuresmentioning
confidence: 99%
“…Following host cell infection, IAV and hCoV utilize several strategies to hamper IFN expression ( Hale et al., 2008b ; Evseev and Magor, 2021 ). Most of these strategies are depending mainly on two non-structural viral protein(s), specifically IAV NS1 and hCoV non-structural protein 1 (Nsp1), that hijack, suppress, or escape the host cell innate immunity antiviral responses via several molecular strategies, including antagonism of IFN production ( Kanrai et al., 2016 ; Petersen et al., 2018 ; Khorramdelazad et al., 2021 ; Kumar et al., 2021a ; Blake et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The structure of the ED domain monomer unit of the NS1 consists of three α-helices and seven β-chains. The protein core is arranged in a long central α-helix surrounded by a twisted antiparallel β-sheet [ 24 ]. The ED structural domain interacts with innate immune response host factors induced by influenza virus infection and plays an important role in RBD localization and nuclear export of NS1.…”
Section: Structure Of the Iav Ns1mentioning
confidence: 99%